Dynamic Angiogenic Switch as Predictor of Response to Chemotherapy-Bevacizumab in Patients With Metastatic Colorectal Cancer. (January 2019) - Cubillo, Antonio; Álvarez-Gallego, Rafael; Muñoz, Manuel; Pond, Gregory; Perea, Sofía; Sánchez, Gema; Martin, María; Rodríguez-Pascual, Jesús; Garralda, Elena; Vega, Estela; de Vicente, Emilio; Quijano, Yolanda; et al.
Abstract : Background: Previous studies have shown that metastatic colorectal carcinoma (mCRC) patients treated with bevacizumab, experience variation in the plasma levels of angiogenesis growth factors and related cytokines, called angiogenic switch (AS). The aim of the present study was to analyze the relationship between AS and the clinical response during standard chemotherapy-bevacizumab treatment. Patients and Methods: Patients with Eastern Cooperative Oncology Group 0-1 mCRC were eligible. Patients received treatment with standard dose capecitabine plus either oxaliplatin or irinotecan and bevacizumab for 6 cycles. Initial treatment was followed by maintenance therapy with bevacizumab plus capecitabine until progression. Plasma levels of angiogenic-related cytokines (hepatocyte growth factor, placental growth factor, macrophage chemoattractant protein-3, MM-9, eotaxin, basic fibroblast growth factor, and interleukin 18) were prospectively analyzed at baseline and every 8 weeks. Progression-free survival (PFS) was calculated using the Kaplan-Meier method. Results: A total of 71 patients were enrolled. AS was observed in 45 patients (63.4%), 28 of whom experienced AS at the first evaluation after treatment start. Disease control, which includes partial/complete response and stable disease, was seen in 96% of AS patients (43/45), but only in 15/26 (58%) for the remaining patients without evidence of AS ( P <0.001). The median PFS of AS patients was 11.4 months (95% confidence interval, 8.6-15.8) versus 8.3 months for patients without AS (95% confidence interval, 5.6-16.4; P =0.04). Conclusions: Chemotherapy plus Bevacizumab combination in mCRC patients results in dynamic changes in plasma cytokines, which is associated with better disease control and longer PFS. These new findings support continuing studying AS as a potential marker of angiogenesis inhibitor effectiveness.